Rebusan Jahe Merah (Zingiber officinale Rosc. var Rubrum) – Kunyit Putih (Curcuma zedoaria Rosc.) sebagai Jamu Peluruh Urin - Sholehuddin, Mohammad; Santoso, Hari; Syauqi, Ahmad (Jurnal SAINS ALAMI (Known Nature), 2018)
A diuretic is a compound that can stimulate urine releasing. The content of gingerol, curcumin and flavonoids in red ginger - white turmeric is thought to be efficacious as urine laxative. This study aims to determine efficacy of red ginger stew - white turmeric as urine laxative and to determine the level of differences in NaCl before and after drinking red ginger stew - white turmeric. The test was carried out by giving one1 cup (250 ml) of red ginger - white turmeric stew every day for 5 days. Using a quasi-experimental method with posttest pretest design was done. Data analysis uses percentage calculation. The results showed that administration of red ginger stew - white turmeric efficacious as a urine laxative which is characterized by increased intensity of urinary discharge, pH and NaCl of urine levels, as well as urine color that is getting transparent and clearer. Keywords: red ginger stew - white turmeric, urine laxative ABSTRAKDiuretikum adalah suatu senyawa yang dapat merangsang pengeluaran urin. kandungan senyawa gingerol, kurkumin dan flavonoid pada  jahe merah – kunyit putih diduga berkhasiat sebagai peluruh urin. Penelitian ini bertujuan untuk mengetahui khasiat rebusan jahe merah - kunyit putih sebagai peluruh urin dan untuk mengetahui kadar perbedaan NaCl sebelum dan sesudah minum rebusan jahe merah – kunyit putih. Pengujian dilakukan dengan pemberian rebusan jahe merah – kunyit putih sebanyak 1 gelas (250 ml) perhari selama 5 hari. Menggunakan metode quasi eksperimen dengan rancangan pre-tes post-test. Analisis data menggunakan perhitungan persentase. Hasil penelitian menunjukkan bahwa pemberian rebusan jahe merah – kunyit putih berkhasiat sebagi peluruh urin, yang ditandai dengan meningkatnya intensitas pengeluaran urin, pH urin dan Kadar NaCl urin, serta warna urin yang semakin muda dan jernih.Kata kunci: rebusan jahe merah – kunyit putih, peluruh urin